PENTINGNYA MENGONSUMSI IKAN BAGI KESEHATAN ANAK DI DESA MAMBALAN KECAMATAN GUNUNGSARI KABUPATEN LOMBOK BARAT: The Importance Of Consuming Fish For Children's Health In Mambalan Village, Gunungsari District, West Lombok Regency - Marini, Ida Ayu Ketut; Artika, Ida Bagus Eka; Sativa, Denianto Yoga; Kalih, L.A.T.T.W. Sukmaring; Dewi, Ni Made Nia Bunga Surya; Rizal, Lalu Samsul; Furkan, Al; Soraya, Indah (Al-Amal: Jurnal Pengabdian Masyarakat, 2025)
The counseling conducted in Mambalan Village located at SD No. 1 Mambalan aims to reduce stunting rates through: educating elementary school students about the benefits of fish for health, fostering children's interest in consuming fish regularly, encouraging healthy living behavior from an early age through nutritious diets. The implementation method is carried out by means of Interactive Counseling, Educational Media, Educational Games and Quizzes and Practice (demonstration). This counseling succeeded in increasing the awareness of students of SD Negeri 1 Mambalan about the importance of fish consumption. It is hoped that activities like this can be carried out periodically and involve the role of parents and the school community so that nutritional messages can be applied in everyday life.